Techno-economic performance of mechanical transplanter for hybrid variety of rice in unpuddled soil (Progressive Agriculture, 2020)
Unpuddled transplanting of rice as a part of conservation agricultural practice has become significant due to its protective behavior for soil properties and economic profitability. Mechanical transplanting in unpuddled soil using hybrid rice variety leads to a high yield with minimum transplanting time and cost, securing soil nutrients. A study was conducted in Bangladesh Agricultural University to evaluate the efficacy of mechanical transplanting of hybrid rice in unpuddled soil considering field and financial performances of rice transplanter. The experiment was conducted during Boro-2018 season with a Daedong DP-480 rice transplanter. Hybrid rice seed Moyna (HTM303) of Laal Teer seed company Ltd. was used for transplanting at a seed rate of 120g per tray and seedling per hill was adjusted to 2-3 nos. In unpuddled soil, transplanter possessed an effective field capacity, fuel consumption and efficiency of 0.16 ha/h, 4.8 l/ha and 67.48%, respectively. Transplanting time included an idle time of 11% due to clogging with mud. Missing hill percentage was found as 6.1% with a floating hill of 7.36%. Plant heights were 15.72 cm and 86.19 cm at the day of transplanting and at the day of harvesting, with tiller per hill of 18 nos. The average panicle length of plants was found as 23.6 cm where traditionally transplanted rice has panicles of 21.2 cm average. The yields of mechanically transplanted rice in unpuddled soil condition was 5.21 ton/ha and the yield of mechanical transplanted rice in unpuddled soil was found to be 27.07% higher than traditionally transplanted rice. The BCR and IRR of mechanical transplanting in unpuddled soil was found 1.57 and 55% considering 10% discount factor. The payback period, after which the transplanter will overcome its costs, was found 1.68 years. Financial analysis reveals that mechanical transplanting with this field capacity will be beneficial if the transplanter is used to transplant 19.77 ha annually.Progressive Agriculture 30 (4): 405-413, 2019